Unleashing open innovation: A decomposition nexus of Sharia-compliant financing and job creation - Sri Budi Cantika Yuli; Mochamad Rofik (Journal of Open Innovation: Technology, Market and Complexity, 2023)
This study investigates the impact of Sharia-compliant financing on job creation in Indonesia. Utilizing provincial-level data and employing fixed effects panel data regression with the GLS estimator, we explore the decomposition effects of Sharia-compliant financing on job creation. Our findings reveal that an increase in the market share of sharia-compliant financing in total, working capital, and consumption does not have a significant impact on job creation. Surprisingly, the share of sharia-compliant financing in investment shows a significant negative impact on job creation. However, it is important to note that overall, Sharia-compliant financing has a positive impact on increasing job creation. Specifically, Sharia-compliant financing for working capital exhibits the highest impact on job creation, followed by Sharia-compliant financing for investment and households. Based on these findings, we propose an open innovation framework to expand the dissemination of Sharia-compliant financing, with a particular focus on MSMEs, with the aim of enabling Islamic banks to play a pivotal role in job creation.